1 |
n+1 |
1 |
2n |
1 |
n+2 |
1 |
2n |
1 |
2n+1 |
1 |
2(n+1) |
则f(n+1)−f(n)=
1 |
2n+1 |
1 |
2(n+1) |
1 |
n+1 |
1 |
2n+1 |
1 |
2(n+1) |
1 |
2n+1 |
1 |
2n+2 |
所以数列f(n)是关于n(n∈N,n≥2)的递增数列,
所以f(n)≥f(2)=
1 |
2+1 |
1 |
2+2 |
1 |
3 |
1 |
4 |
7 |
12 |
所以要使不等式
1 |
n+1 |
1 |
n+2 |
1 |
2n |
7 |
12 |
故选C.
1 |
n+1 |
1 |
n+2 |
1 |
2n |
1 |
3 |
1 |
2 |
7 |
12 |
1 |
n+1 |
1 |
2n |
1 |
n+2 |
1 |
2n |
1 |
2n+1 |
1 |
2(n+1) |
1 |
2n+1 |
1 |
2(n+1) |
1 |
n+1 |
1 |
2n+1 |
1 |
2(n+1) |
1 |
2n+1 |
1 |
2n+2 |
1 |
2+1 |
1 |
2+2 |
1 |
3 |
1 |
4 |
7 |
12 |
1 |
n+1 |
1 |
n+2 |
1 |
2n |
7 |
12 |